MILLENIALS IN VISUAL: APPOINTMENT OF EDUCATIONAL ISSUES IN INDONESIA THROUGH DIGITAL STRIP COMIC ON INSTAGRAM - Muhsinah Annisa; Fadhlan Muchlas Abrori; Rumansyah Rumansyah; Asrani Asrani; Herti Prastitasari (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2020)
The purpose of this study is to describe students' responses and reactions regarding digital comics using the Instagram platform. The approach in this research is qualitative with descriptive research type. Data collection was carried out through a survey of 50 students at the University of Borneo Tarakan and 119 students from the University of Lambung Mangkurat. The results of student responses and reactions were positive. Students respond to comics in terms of format and relevance. Meanwhile, students react to comics based on attractiveness and satisfaction. Research is limited to describing students' responses and reactions, without measuring the effectiveness of comics in learningKeywords: Digital Comics Strip, Instagram, Respons, Reaction